2020
DOI: 10.1016/j.mayocpiqo.2020.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Serial Amnioinfusion as Regenerative Therapy for Pulmonary Hypoplasia in Fetuses With Intrauterine Renal Failure or Severe Renal Anomalies: Systematic Review and Future Perspectives

Abstract: The aim of this study was to investigate the effect of serial amnioinfusion therapy (SAT) for pulmonary hypoplasia in lower urinary tract obstruction (LUTO) or congenital renal anomalies (CRAs), introduce patient selection criteria, and present a case of SAT in bilateral renal agenesis. We conducted a search of the MEDLINE, EMBASE, Web of Science, and Scopus databases for articles published from database inception to November 10, 2017. Eight studies with 17 patients (7 LUTO, 8 CRA, and 2 LUTO þ CRA) were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
(92 reference statements)
0
4
0
2
Order By: Relevance
“…Двусторонняя агенезия почек встречается с частотой около 1-3 на 10 000 новорожденных [4,7,8]. Помимо синдрома Поттера, ДПА может включаться в состав более 70 синдромов и клинических состояний (Майер -Рокитанского -Кюстер -Хаузера, Паллистера -Холла, гетеротаксия и др.)…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Двусторонняя агенезия почек встречается с частотой около 1-3 на 10 000 новорожденных [4,7,8]. Помимо синдрома Поттера, ДПА может включаться в состав более 70 синдромов и клинических состояний (Майер -Рокитанского -Кюстер -Хаузера, Паллистера -Холла, гетеротаксия и др.)…”
Section: Discussionunclassified
“…К тому же на сегодняшний день известно лишь об одном выжившем ребенке в возрасте 9 мес., перенесшем серийные амниоинфузии и находящемся на перитонеальном диализе, в ожидании трансплантации почек. Таким образом, учитывая отсутствие доказательной базы и отсроченных результатов, а также психологические и этические аспекты САИ, данный вид вмешательства пока не может рассматриваться в качестве метода лечения детей с синдромом Поттера [2,4,6,8,[15][16][17].…”
Section: Discussionunclassified
“…A systemic review was performed by Warring, et al on serial amnioinfusion therapy, in cases of oligohydramnios diagnosed at early gestational age secondary to LUTO or chronic renal anomalies. The review concluded serial amnioinfusion therapy can reduce the risk of newborn mortality due to pulmonary compromise [10].…”
Section: Discussionmentioning
confidence: 99%
“…There is no clear standard of care for kidney agenesis and neonatal end-stage kidney failure. To our knowledge, there have been 11 published clinical case reports of anhydramnios successfully treated by amnioinfusion to promote lung development and allow sufficient pulmonary function to survive the immediate postnatal period . However, the majority of these cases fail to fully address these infants’ long-term kidney failure and their dialysis outcomes.…”
mentioning
confidence: 99%